How does aquatic macrophyte Salvinia auriculata respond to nanoceria upon an increased CO2 source? A Fourier transform-infrared photoacoustic spectroscopy and chlorophyll a fluorescence study - Pontes, Montcharles S.; Grillo, Renato [UNESP]; Graciano, Daniela E.; Falco, William F.; Lima, Sandro M.; Caires, Anderson R.L.; Andrade, Luís H.C.; Santiago, Etenaldo F. (Elsevier, 2019)
With the continued increase of technological uses of cerium oxide nanoparticles (CeO2 NPs or nanoceria)and their unregulated disposal, the accumulation of nanoceria in the environment is inevitable. Concomitantly, atmospheric carbon dioxide (CO2)levels continue to rise, increasing the concentrations of bicarbonate ions in aquatic ecosystems. This study investigates the influence of CeO2 NPs (from 0 to 100 μgL−1)in the presence and absence of an elevated bicarbonate (HCO3 −)ion concentration (1 mM), on vibrational biochemical parameters and photosystem II (PSII)activity in leaf discs of Salvinia auriculata. Fourier transform-infrared photoacoustic spectroscopy (FTIR-PAS)was capable of diagnostic use to understand biochemical and metabolic changes in leaves submitted to the CeO2 NPs and also detected interactive responses between CeO2 NPs and HCO3 − exposure at the tissue level. The results showed that the higher CeO2 NPs levels in the presence of HCO3 − increased the non-photochemical quenching (NPQ)and coefficient of photochemical quenching in dark (qPd)compared to the absence of HCO3. Moreover, the presence of HCO3 − significantly decreased the NPQ at all levels of CeO2 NPs demonstrating that HCO3 − exposure may change the non-radiative process involved in the operation of the photosynthetic apparatus. Overall, the results of this study are useful for providing baseline information on the interactive effects of CeO2 NPs and elevated HCO3 − ion concentration on photosynthetic systems.
Keywords: Biochemical responses; CeO2 nanoparticles; CO2; Emerging contaminant; Photosynthetic activity